Etiological findings in cases with incidental liver metastasis and factors affecting survival (Annals of Medical Research, 2022)
Aim: In this study, the general characteristics of incidental liver metastasis and the factors affecting survival were investigated.Materials and Methods: In our study, we retrospectively analyzed 216 patients with metastases in the liver at diagnosis. Patients with previously known primary malignancy and liver failure due to chronic viral hepatitis were excluded from the study.Results: The etiological causes of metastatic liver lesions were cancer of unknown primary (CUP) 27.78%, pancreato biliary region tumors ( PBRT) 19.44%, colorectal cancer (CRC) 18.98% and 12.96% gastric cancer, in order of frequency.  No significant correlation was found in the concordance analysis between CT and USG in detecting metastases  In the survival analysis, higher alanine aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), gamma-glutamyl transpeptidase (GGT), cancer antigen 19-9 (CA 19-9), total bilirubin (TBIL), direct bilirubin (DBIL)  levels and lower albumin levels were found to be statistically significant in patients who died compared to aliving patients (p
Keywords: Liver metastasis; unknown primary cancer; prognosis; tumor markers